EFFECT OF THREE FODDER TREES ON Haemonchus contortus CONTROL AND WEIGHT VARIATIONS IN KIDS - Castro-León, Yesenia; Olivares Pérez, Jaime; Rojas-Hernández, Saúl; Villa-Mancera, Abel; Valencia-Almazán, Ma Trinidad; Hernández-Castro, Elías; Córdova-Izquierdo, Alejandro; Jiménez-guillen, Régulo (Ecosistemas y Recursos Agropecuarios, 2015)
The objective was to evaluate the activity against Haemonchus contortus by foliage taken from three tanniferous tree species and fed to Creole male kids experimentally infected with a dose of 350 larvae of H. contortus (L3) kg-1 body weight (BW). Twenty Creole kids weighing 12 ± 2.0 kg were randomly distributed in four treatments: T1 = control without foliage, and the addition of fresh foliage (10 % of the dry matter of the total diet) of Guazuma ulmifolia (T2), Pithecellobium dulce (T3) and Acacia cochliacantha (T4). For sixty days, the activity of the foliage against H. contortus was evaluated by quantifying the reduction in the excretion of eggs per gram of feces; also, the excretion of eggs was associated with the concentration of the blood cell pack, dry matter intake and weight change in animals. The data of the evaluated variables were analyzed in a completely randomized design and a Tukey test was carried out for comparison of means (p < 0.05). The secondary compounds of P. dulce and A. cochliacanta foliage were more effective (p < 0.04) in the control of H. contortus with minor excretion of eggs (1.48 and 1.18 Log10 g-1 of feces), respectively. The hematocrit was different (p < 0.005) mainly in hemoglobin, erythrocytes, lymphocytes and eosinophils; dry matter intake (p < 0.05) and changes in total body weight (p < 0.01) were higher in kids which received P. dulce foliage (T3) with 621.5 g d-1 and 2.4 kg, respectively. It was concluded that the secondary compounds of fresh P. dulce and A. cochliacantha foliage have the potential to control H. contortus without affecting the health and productive response in kids.